Ahmad Amin's Concept of Ethics and Its Relevance to Social Welfare - Dendy Wahyu Anugrah (Journal of Islamic Thought and Contemporary Studies, 2025)
Ethics is a fairly central and important discussion in people's lives. This is because in a community, there are ethical values that guide a society to try to realise social welfare. Therefore, it is interesting to study further how ethics can be used as a guideline to realise the noble ideals of the community. Therefore, this research aims to review one of the contemporary ethical thinkers from Egypt, Ahmad Amin, and explain how his thoughts are relevant in realising social welfare. The research method used in this research is the library research method with the source of the book Etika: Ilmu Akhlak (1986) by Ahmad Amin. Thus, this research concludes that Ahmad Amin's ethical thinking has relevance to the realisation of the social welfare of community life, especially when individual rights and obligations are implemented properly.